PENGARUH MANAJEMEN MODAL KERJA, LIKUIDITAS, AKTIVITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2015-2019 - Irmawati Irmawati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of working capital, liquidity ratio, activity and solvency on profitability in manufacturing companies listed on the Indonesia Stock Exchange. This type of research is a quantitative study using secondary data analysis in the form of financial statements of companies listed on the Indonesian stock exchange for the 2015-2019 period. Research sample is 14 manufacturing Company. Determination of the sample in this study using purposive sampling method. Data analysis used classical assumption test and multiple linear analysis. The independent variables used in this study are working capital (X1), liquidity (X2) activity (X3), and solvency (X4), while the dependent variable is profitability (Y). The results of the study show that: 1) Working Capital has no significant effect on Profitability,2) liquidity has no significant effect on Profitability. 3) Activity has positive and significant effect influence on profitability (4) Solvency is a negative and significant effect on Profitability